2022
DOI: 10.3389/fmed.2021.676461
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Algorithms for the Prediction of Posttransplant Renal Function in Deceased-Donor Kidney Recipients: A Preliminary Study Based on Pretransplant Biopsy

Abstract: BackgroundPosttransplant renal function is critically important for kidney transplant recipients. Accurate prediction of graft function would greatly help in deciding acceptance or discard of allocated kidneys.Methods: Whole-slide images (WSIs) of H&E-stained donor kidney biopsies at × 200 magnification between January 2015 and December 2019 were collected. The clinical characteristics of each donor and corresponding recipient were retrieved. Graft function was indexed with a stable estimated glomerula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Luo et al [ 35 ] used donor kidney biopsy WSIs as a source of features in addition to clinical characteristics for graft function prediction, building neural network models to predict stable eGFR and reduced graft function (RGF) in deceased-donor kidney transplant recipients who underwent pre-transplantation biopsy. They tested six prediction models on 219 WSIs.…”
Section: Resultsmentioning
confidence: 99%
“…Luo et al [ 35 ] used donor kidney biopsy WSIs as a source of features in addition to clinical characteristics for graft function prediction, building neural network models to predict stable eGFR and reduced graft function (RGF) in deceased-donor kidney transplant recipients who underwent pre-transplantation biopsy. They tested six prediction models on 219 WSIs.…”
Section: Resultsmentioning
confidence: 99%
“… 48 Although we addressed missingness with multiple imputation, there is the possibility that our outcomes may have differed with a more complete dataset. Finally, we were pragmatic in our selection of donor variables in cluster derivation and added information on donor organs (including pretransplant biopsy results 49 ) may have better predicted death/graft failure. However, these data were not available in our derivation cohort, and our intended purpose was to use factors readily available in other registry databases.…”
Section: Discussionmentioning
confidence: 99%
“…One reason might be the lack of large cohorts needed to train such models. The currently largest kidney biopsy classification study showed the feasibility of predicting kidney allograft diseases from WSI of periodic acid-schiff (PAS), Hematoxylin and Eosin (HE), and Silver-stained biopsies [25 As a proof-of-concept, this study only predicted low-granular classes, that is, biopsies that are normal, show rejection or other diseases. The study showed that such a model could be used for prioritization of biopsies for diagnostics, that is, prioritizing biopsies with rejection and other diseases over normal ones to be handled by a nephropathologist as first.…”
Section: Andandmentioning
confidence: 99%
“…Regression studies based on imaging data in nephropathology are less common in comparison with the number of segmentation and classification studies, however, it is possible to extract information from an image using feature extractors like CNN-based abstract feature extractors and combine this information with the features from other modalities such as features extracted from encoding the clinical data of each donor and the corresponding recipient and passing the combined features to a layer with one neuron to regress the estimated glomerular filtration rate (eGFR) values for post-transplant recipient [26 ▪ ].…”
Section: Deep Learning Applications In Nephropathologymentioning
confidence: 99%